2020
DOI: 10.1038/s41598-020-74712-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of ACTH on collagenase-induced peri-intraventricular hemorrhage in newborn male rats

Abstract: Peri-intraventricular hemorrhage (PIVH) is a common and serious prematurity-related complication in neonates. Adrenocorticotropic hormone (ACTH) has neuroprotective actions and is a candidate to ameliorate brain damage following PIVH. Here, we tested the efficacy of ACTH1-24 on a collagenase-induced lesion of the germinal matrix (GM) in newborn male rats. Animals received microinjection of the vehicle (PBS, 2 µl) or collagenase type VII (0.3 IU) into the GM/periventricular tissue on postnatal day (PN) 2. Twelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Thus, these treatments are only palliative and can only prevent some PHH-associated damage. Treatments are also being sought to prevent the development of GMH, although the molecular causes of its development are not well understood 35,36 . Attempts to develop (which was not certified by peer review) is the author/funder.…”
Section: Germinalmentioning
confidence: 99%
“…Thus, these treatments are only palliative and can only prevent some PHH-associated damage. Treatments are also being sought to prevent the development of GMH, although the molecular causes of its development are not well understood 35,36 . Attempts to develop (which was not certified by peer review) is the author/funder.…”
Section: Germinalmentioning
confidence: 99%
“…ACTH has been found to promote oligodendrocyte protection ( 103 ) and neuron protection from inflammatory, excitotoxic, and apoptotic damages ( 104 , 105 ). Dated research showed that rat embryo neurons respond to ACTH displaying a denser neuritic network ( 106 ) and displayed neuroprotective effects after hemorrhage insult by activating anti-inflammatory pathways ( 107 , 108 ). Melanocortins have been proposed as therapy for brain injuries and several chronic neurodegenerative disorders ( 102 ).…”
Section: Extra-adrenal Effects Of Acthmentioning
confidence: 99%
“…Studies showed that ACTH promotes the differentiation of oligodendroglial progenitor cells to oligodendrocytes accompanied by increased myelination and protects the progenitor cells from excitotoxic and inflammation-related damage ( 32 ). In a rat model of intraventricular hemorrhage, ACTH showed neuroprotective effects in newborn rats ( 33 ).…”
Section: Introductionmentioning
confidence: 99%